Variants in the coagulation factor 2 receptor (F2R) gene influence the risk of myocardial infarction in men through an interaction with interleukin 6 serum levels - Gigante, Bruna; Vikström, Max; Meuzelaar, Linda Strömqvist; Chernogubova, Ekaterina; Silveira, Angela; van’t Hooft, Ferdinand; Hamsten, Anders; Faire, Ulf de (Thrombosis and Haemostasis, 2009)
Thrombin-activated factor 2 receptor (F2R) links thrombosis to inflammation modulating interleukin (IL)6 synthesis. We have investigated the role of F2R genetic variants and their interaction with IL6 serum levels in the occurrence of myocardial infarction (MI) in the Stockholm Heart Epidemiology Program (SHEEP). Seven SNPs –1738 G/A, –506-/GGCCGCGGGAAGC (D/I), 2860 G/A, 2930 T/C, 9113 C/A, 9333 C/T and 120813 T/C within F2R locus were genotyped in the SHEEP (n=2,774). The C allele at position 2930 was associated with a slight reduction in MI risk in men. IL6 serum levels were higher in male cases carrying genotypes AA at the –1738 (p= 0.01) and GG at the 2860 loci (p= 0.03) and both alleles were found to differentially modulate IL6 serum levels in the context of selective haplotypes. High IL6 serum levels (>75th percentile), were independently associated with an increased risk of MI in men with an odds ratio (OR) (95% confidence interval [CI]) of 2.44 (1.72–3.46), (p=0.0016), but not in women ( OR 0.83 [95%CI 0.50–1.36], p=0.64). In the presence of high IL6 serum levels, the –1738A allele increased and the 2860A allele reduced the risk of MI (all p≤0.02). Consistently, the AG diplotype increased MI risk (OR 1.71 [95%CI 1.17–2.51], p=0.005). The –1738 and 2860 loci association with IL6 serum levels was replicated in men in the Stockholm Coronary Artery Risk Factor (SCARF) study (both p≤0.04). In the pooled data from the two populations, the A and G allele modulated the risk of MI in men with high IL6 serum levels (p≤0.03). Our results demonstrate that in men F2R genetic variants influence the risk of MI mainly through an interaction with IL6 serum levels.
Keywords: Thrombin; cytokines; atherothrombosis; epidemiological studies; myocardial infarction